Statistical and Probabilistic Risk Assessment for an Induced Gas Explosion on an Offshore Platform - Kang, KiYeob (Curtin University, 2019)
The purpose of this research was to investigate the influence of explosion wave on structural integrity in terms of risk assessment concept. It was a computational analysis study that covered how explosion wave pressure could be changed according to several variables, and how dangerous it is in terms of structural physical damage. By using relevant theories and techniques, the extent of explosion risk was assessed based on both quantitative and qualitative methodologies.